Who Adjusts? Domestic Sources of Foreign Economic Policy during the Interwar Years - Simmons, Beth A. (Princeton studies in international history and politics., 2020)
In this work Beth Simmons presents a fresh view of why governments decided to abide by or defect from the gold standard during the 1920s and 1930s. Previous studies of the spread of the Great Depression have emphasized "tit-for-tat" currency and tariff manipulation and a subsequent cycle of destructive competition. Simmons, on the other hand, analyzes the influence of domestic politics on national responses to the international economy. In so doing, she powerfully confirms that different political regimes choose different economic adjustment strategies.